Preparation method of anode catalyst of direct hydroboron fuel cell and preparation method of anode

By performing specific ball milling treatment on cast iron-boron alloys and mixed pressing with carbonyl nickel powder, an efficient iron-boron alloy anode electrode was prepared, which solved the problems of low electron release number and high catalyst cost caused by hydrolysis reaction in DBFC, and achieved Efficient catalytic properties and cheap materials applications.

CN119319250APending Publication Date: 2025-01-17INNER MONGOLIA NORMAL UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411402300.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

In direct borohydride fuel cells (DBFCs), the hydrolysis reaction of the anode catalyst results in low electron release numbers, affecting fuel utilization, and existing nickel-based and cobalt-based catalysts are costly and lack of cheap alternative materials.

Method used

A planetary ball mill is used to perform ball milling of cast iron-boron alloys for 60 to 80 cycles, and the ball milling medium and time are controlled to obtain iron-boron alloy powder with high catalytic properties, and then mixed with carbonyl nickel powder and pressed into an anode electrode.

Benefits of technology

It improves the oxidation peak current density, stable current density and power density of the anode catalyst, reduces the open circuit potential, provides cheap and efficient catalytic performance, and opens up a new direction for the application of iron-based materials in DBFC.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119319250A_ABST
    Figure CN119319250A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an anode catalyst of a direct hydroboron fuel cell and a preparation method of an anode. A preparation method of an anode catalyst of a direct hydroboron fuel cell comprises the following steps: carrying out ball milling on as-cast iron-boron alloy for 60-80 cycles by adopting a planetary ball mill to obtain a ball-milled sample; drying the ball-milled sample to obtain iron-boron alloy powder used as the anode catalyst of the direct hydroboron fuel cell; wherein the mass ratio of Fe to B in the as-cast iron-boron alloy is (3.5-4.0): 1; the ball-milling medium is absolute ethyl alcohol, the ball-to-material ratio is (3.5-4.5): 1, and the ball-milling rotating speed is 300-400 rpm; one period is set as follows: the planetary ball mill rotates forwards for 18-22 min and stands for 7-11 min, and then the planetary ball mill rotates reversely for 18-22 min and stands for 7-11 min. The method disclosed by the invention is beneficial to improving the catalytic performance of the obtained anode catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing an anode catalyst of a direct borohydride fuel cell and a method for preparing an anode, and in particular to a method for preparing an anode catalyst of a direct borohydride fuel cell and a method for preparing an anode of a direct borohydride fuel cell. Background Art

[0002] Hydrogen fuel cells represent the efficient use of hydrogen energy. Compared with traditional fossil fuel engines, hydrogen fuel cells have the advantages of no pollutant emissions, low noise, high energy conversion efficiency, and fast system response. In recent years, people have designed fuel cells using alkaline solutions of borohydrides (KBH4, NaBH4) directly as fuel and O2 as oxidant to obtain direct borohydride fuel cells (DBFC).

[0003] DBFC is a kind of material that is stored in borohydride (BH4 - A new type of fuel cell that directly converts the chemical energy (hydrogen energy) in hydrogen into electrical energy under the action of an anode catalyst. DBFC has a higher output voltage and energy density than general fuel cells. At the same time, this type of battery also has the advantages of being able to work at room temperature and being safe for transportation. Therefore, it is considered to be a new type of hydrogen fuel cell with great appeal and application potential, and will receive more and more attention.

[0004] During the operation of DBFC, BH4 in the borohydride on the anode - An oxidation reaction (Borohydride Oxidation Reaction, BOR) occurs, and the oxygen or hydrogen peroxide on the cathode undergoes a reduction reaction (Oxygen Reduction Reaction ORR). The corresponding electrode reaction equations are shown in (1) to (3):

[0005] Anode reaction: BH4 - +8OH - →BO2 - +6H2O+8e - (1)

[0006] E o anode =-1.24V(vs.SHE)

[0007] Cathode reaction: 2O2+4H2O+8e - →8OH - (2)

[0008] E o cathode =0.4V(vs.SHE)

[0009] Total battery reaction: BH4- +2O2→BO2 - +2H2O(3),

[0010] E o cell =1.64V

[0011] From the above reaction equation, we can see that theoretically, each BH4 involved in the reaction - Complete reaction under the action of anode catalyst can release 8e - But in the actual work of DBFC, BH4 - Under the action of the anode catalyst, an oxidation reaction also occurs during hydrolysis to release hydrogen, so that the number of electrons released is often less than 8e - , which reduces the utilization rate of fuel. The hydrolysis reaction equation is:

[0012] BH4 - + 2H2O → BO2 - + 4H2↑ (4),

[0013] Taking into account the occurrence of hydrolysis, in fact, the overall reaction equation occurring at the anode of a general DBFC is:

[0014] BH4 - +xOH - → BO2 - + (x-2) H2O + (4-x) H2↑ + xe - (5)

[0015] In the formula, x is the actual reaction process of each BH4 - The number of electrons released. It can be seen that the value of x depends on the intensity of the hydrolysis reaction, which is directly controlled by the anode catalyst. In other words, the anode catalyst is the key factor in determining the number of electrons released by DBFC. Therefore, it is crucial to find an anode catalyst with good catalytic performance, the ability to inhibit hydrolysis side reactions, and low price for the development of DBFC.

[0016] Initially, researchers mostly used noble metals and their alloys as anode catalysts for DBFCs, but the high cost of noble metal catalysts limited their widespread application. In order to further improve the performance of anode catalysts and reduce the cost of catalysts, researchers have been working hard to find a class of non-noble metal anode catalysts. In recent years, research on nickel-based and cobalt-based transition metal catalysts has been more extensive. Both cobalt and nickel can be used as anode catalysts for DBFCs.

[0017] CN101667645A discloses the application of a Ni-based catalyst in a direct borohydride fuel cell anode, wherein the active components of the catalyst are composed of Ni and one or more metal elements from groups IB and VIII B, the percentage of the active components in the catalyst is 5% to 80%, and the remainder is a C carrier.

[0018] CN105655601A discloses a method for preparing a direct borohydride fuel cell anode catalyst, the preparation method comprising: taking Co 2+ solution, adding ammonia water thereto and stirring until the pH value is 8.5-9 to obtain a mixed solution, and performing solid-liquid separation on the mixed solution; taking the separated solid phase, washing, drying, grinding and roasting in sequence to obtain a direct borohydride fuel cell anode catalyst.

[0019] CN113410476A discloses a method for preparing a La-Mg-Ni type hydrogen storage alloy modified by Ag, comprising the following steps: (1) Preparation of La-Mg-Ni type hydrogen storage alloy: induction melting of rare earth metal La, metal Co, Mn, Al and intermediate alloy Mg2.5Ni to prepare La-Mg-Ni type hydrogen storage alloy; (2) Preparation of polyvinyl alcohol (PVP) + AgNO3 / La-Mg-Ni mixture: a. preparing polyvinyl alcohol (PVP) sol; b. preparing AgNO3 solution; c. preparing polyvinyl alcohol (PVP) + AgNO3 / La-Mg-Ni mixture; (3) Preparation of Ag-modified La-Mg-Ni type hydrogen storage alloy: placing the polyvinyl alcohol (PVP) + AgNO3 / La-Mg-Ni mixture prepared in step (2) under ultraviolet xenon lamp for irradiation to obtain Ag-modified La-Mg-Ni type hydrogen storage alloy. The Ag-modified La-Mg-Ni type hydrogen storage alloy can be used as an anode catalyst for direct borohydride fuel cells.

[0020] CN111952609A discloses a method for preparing an anode catalyst for a direct borohydride fuel cell, comprising: (1) using metal Ni, Co, Mn, Al and mixed rare earth Mm as raw materials, wherein Mm is composed of 63.1wt.% La, 26.0wt.% Ce, 2.7wt.% Pr and 8.2wt.% Nd, and smelting in a non-consumable vacuum arc furnace at a smelting temperature higher than the melting point of each metal to obtain Mm 1-x Ni 2.485 Co 0.525 Mn 0.28 Al 0.21 , x = 0.1-0.5 alloy; (2) the Mm prepared by the above smelting 1- x Ni 2.485 Co 0.525 Mn0.28 Al 0.21 The alloy is crushed and mixed with Mg powder, and the mixing ratio is (Mm 1-x Mg x )Ni 2.485 Co 0.525 Mn 0.28 Al 0.21 , wherein x=0.1-0.5, and the mixture is mechanically ball milled using a high-energy vibration ball mill.

[0021] Compared with existing nickel-based and cobalt-based materials, iron-based materials are cheaper. However, so far, there are still no reports on the use of iron-based materials as anode catalysts for direct borohydride fuel cells. Summary of the invention

[0022] In view of this, one object of the present invention is to provide a method for preparing an anode catalyst for a direct borohydride fuel cell, which can effectively improve the catalytic performance of the obtained iron-boron alloy powder used as an anode catalyst for a direct borohydride fuel cell through a specific ball milling method and ball milling time. Another object of the present invention is to provide a method for preparing an anode for a direct borohydride fuel cell. The present invention adopts the following technical solution to achieve the above object.

[0023] In one aspect, the present invention provides a method for preparing an anode catalyst for a direct borohydride fuel cell, comprising the following steps:

[0024] The cast iron-boron alloy is ball-milled by a planetary ball mill for 60 to 80 cycles to obtain a ball-milled sample; the ball-milled sample is dried to obtain an iron-boron alloy powder used as an anode catalyst for a direct borohydride fuel cell;

[0025] Wherein, the mass ratio of Fe to B in the cast iron-boron alloy is 3.5-4.0:1;

[0026] The ball milling medium is anhydrous ethanol, the ball-to-material ratio is 3.5-4.5:1, and the ball milling speed is 300-400 rpm;

[0027] Among them, one cycle is set to first make the planetary ball mill rotate forward for 18 to 22 minutes, stand for 7 to 11 minutes, and then make the planetary ball mill reverse for 18 to 22 minutes, and stand for 7 to 11 minutes.

[0028] According to the preparation method of the present invention, preferably, the cast iron-boron alloy is ball-milled for 70 to 80 cycles using a planetary ball mill.

[0029] According to the preparation method of the present invention, preferably, in the cast iron-boron alloy, the mass ratio of Fe to B is 3.6-3.9:1.

[0030] According to the preparation method of the present invention, preferably, the ball-to-material ratio is 3.7-4.2:1.

[0031] According to the preparation method of the present invention, preferably, during ball milling, a mixture of large steel balls and small steel balls is used, the diameter of the large steel balls is 8-10 mm, and the diameter of the small steel balls is 4-6 mm.

[0032] According to the preparation method of the present invention, preferably, the ball milling speed is 300-350 rpm.

[0033] According to the preparation method of the present invention, preferably, one cycle is set to first rotate the planetary ball mill forward for 19 to 21 minutes, stand for 9 to 11 minutes, then reverse the planetary ball mill for 19 to 21 minutes, and stand for 9 to 11 minutes.

[0034] On the other hand, the present invention also provides a method for preparing an anode of a direct borohydride fuel cell, comprising the following steps:

[0035] (1) preparing an iron-boron alloy powder used as an anode catalyst for a direct borohydride fuel cell according to the preparation method described above;

[0036] (2) mixing the iron-boron alloy powder and carbonyl nickel powder obtained in step (1) to obtain a mixture; loading the mixture into a cylindrical mold and then pressing it into a disc; wrapping the disc with nickel foam, and then clamping one end of a nickel strip used as an electrode lead between the nickel foams and spot welding it around to obtain an electrode used as an anode; wherein the mass ratio of the iron-boron alloy powder to the carbonyl nickel powder is 1:2.9-3.2.

[0037] According to the preparation method of the present invention, preferably, the pressure during pressing is 10-15 MPa, and the pressing time is 15-20 min.

[0038] According to the preparation method of the present invention, preferably, the loading amount of the iron-boron alloy powder as the anode catalyst of the direct borohydride fuel cell in the wafer is 114-116 mg / cm 2 .

[0039] The present invention can improve the catalytic performance of the obtained iron-boron alloy powder used as an anode catalyst of a direct borohydride fuel cell by controlling a specific ball milling method and ball milling time, and the oxidation peak current density value, the stable current density value, and the power density value are all large, and the open circuit potential is small. The present invention provides a new idea for the research of anode catalysts of direct borohydride fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] FIG. 1( a ) shows the X-ray diffraction (XRD) results of the products of the examples and comparative examples.

[0041] FIG1( b ) is an enlarged view of FIG1( a ).

[0042] FIG. 2( a ) is a SEM result of the iron-boron alloy powder of Comparative Example 1. FIG.

[0043] FIG. 2( b ) is the SEM result of the iron-boron alloy powder of Comparative Example 2. FIG.

[0044] FIG. 2( c ) is the SEM result of the iron-boron alloy powder of Comparative Example 3. FIG.

[0045] FIG. 2( d ) is the SEM result of the iron-boron alloy powder of Example 1. FIG.

[0046] FIG. 2( e ) is the SEM result of the iron-boron alloy powder of Example 2.

[0047] FIG. 2( f ) is the SEM result of the iron-boron alloy powder of Comparative Example 4. FIG.

[0048] FIG. 3( a ), FIG. 3( b ), and FIG. 3( c ) are the mapping results of Comparative Example 1. FIG.

[0049] Figure 3(d), Figure 3(e), and Figure 3(f) are the mapping results of Example 2.

[0050] FIG3( g ) is the EDS spectrum result of Comparative Example 1.

[0051] Figure 4 CV curve results of each product in Experimental Example 1.

[0052] Figure 5 The CA curve results of each product in Experimental Example 1 are shown in FIG.

[0053] Figure 6 : This is the EIS Nyquist plot of each product in Experimental Example 1.

[0054] Figure 7 This is the polarization curve of the single cell formed by Fe-B0 and Fe-B8 in Experimental Example 2. DETAILED DESCRIPTION

[0055] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0056] In the prior art, non-precious metal catalysts generally use nickel boron or cobalt boron materials, and other metal elements (such as precious metals Pt, Au, rare earth elements and Cu, Zn, etc.) are added on the basis of nickel boron or cobalt boron, which are often referred to as nickel-based or cobalt-based catalyst materials. Compared with iron-based materials, the cost of nickel-based or cobalt-based materials is higher. In addition, the synthesis of nickel-based or cobalt-based materials mostly adopts chemical methods, and the amount ratio of nickel boron or cobalt boron cannot be accurately controlled in actual production. Only after obtaining a product that can be used as an anode catalyst, the content of nickel boron or cobalt boron in the product can be measured, and the mass ratio of nickel boron or cobalt boron can be accurately known, which is not conducive to the controllable preparation of catalysts. For the above reasons, and based on a large number of studies by the inventors in direct borohydride fuel cells, the inventors boldly and innovatively propose to replace nickel or cobalt elements with iron elements, and use them as anode catalysts of direct borohydride fuel cells, which can provide a new idea and new direction for the research of anode catalysts of direct borohydride fuel cells.

[0057] The present invention provides a method for preparing an anode catalyst for a direct borohydride fuel cell, comprising the following steps: (1) a ball milling step; and (2) a drying step, which is described in detail below.

[0058] <Ball milling step>

[0059] The cast iron-boron alloy is ball-milled for 60 to 80 cycles using a planetary ball mill to obtain a ball-milled sample, which is beneficial to improving the catalytic performance of the obtained iron-boron alloy powder used as an anode catalyst for a direct borohydride fuel cell.

[0060] In the present invention, the cast iron-boron alloy can be purchased commercially. The mass ratio of Fe to B in the cast iron-boron alloy is 3.5 to 4.0:1, preferably 3.6 to 3.9:1, and more preferably 3.7 to 3.85:1. In the present invention, B is boron.

[0061] In the present invention, the planetary ball mill used may be a known one.

[0062] During ball milling, steel balls are used, and a mixture of large and small steel balls is used. The diameter of the large steel balls is 8 to 10 mm, and the diameter of the small steel balls is 4 to 6 mm. The mass ratio of all large steel balls to all small steel balls can be 0.7 to 1:1, preferably 0.75 to 0.9:1. The ball-to-material ratio is 3.5 to 4.5:1, preferably 4 to 4.5:1. The ball-to-material ratio refers to the ratio of the mass of the steel balls to the mass of the cast iron-boron alloy. The ball milling medium is anhydrous ethanol. The ball milling speed is 300 to 400 rpm, preferably 300 to 380 rpm, more preferably 300 to 350 rpm, and further preferably 320 to 350 rpm.

[0063] In the present invention, the ball milling is performed for 60 to 80 cycles, preferably 70 to 80 cycles, and more preferably 75 to 80 cycles. Among them, one cycle is set to first make the planetary ball mill rotate forward for 18 to 22 minutes, stand for 7 to 11 minutes, and then reverse the planetary ball mill for 18 to 22 minutes, and stand for 7 to 11 minutes. Preferably, one cycle is set to first make the planetary ball mill rotate forward for 19 to 21 minutes, stand for 9 to 11 minutes, and then reverse the planetary ball mill for 19 to 21 minutes, and stand for 9 to 11 minutes. More preferably, one cycle is set to first make the planetary ball mill rotate forward for 20 to 21 minutes, stand for 9 to 10 minutes, and then reverse the planetary ball mill for 20 to 21 minutes, and stand for 9 to 10 minutes. This is conducive to obtaining an iron-boron alloy powder with better catalytic performance as an anode catalyst for a direct borohydride fuel cell. After extensive research and experiments, the present invention has found that such ball milling method and ball milling time are conducive to obtaining an anode catalyst with better catalytic performance. If the ball milling method and ball milling time of the present invention are not adopted, the catalytic performance of the obtained iron-boron alloy powder will be significantly reduced.

[0064] <Drying Step>

[0065] The ball milled sample is dried to obtain an iron-boron alloy powder used as an anode catalyst for a direct borohydride fuel cell, which is conducive to obtaining an anode catalyst with stable performance.

[0066] The drying can be carried out in a vacuum drying oven at a temperature of 35 to 60° C., preferably 40 to 60° C., more preferably 40 to 50° C. The drying time can be 5 hours or more, preferably 7 hours or more, more preferably 8 hours or more, and further preferably 8 to 10 hours.

[0067] The present invention also provides a method for preparing an anode of a direct borohydride fuel cell, comprising the following steps:

[0068] (1) preparing an iron-boron alloy powder used as an anode catalyst for a direct borohydride fuel cell according to the preparation method described above;

[0069] (2) The iron-boron alloy powder and the carbonyl nickel powder obtained in step (1) are mixed to obtain a mixture; the mixture is loaded into a cylindrical mold and then pressed into a disc; the disc is wrapped with nickel foam, and then one end of a nickel strip used as an electrode lead is clamped between the nickel foams and fixed by spot welding around it to obtain an electrode as an anode.

[0070] The mass ratio of the iron-boron alloy powder to the carbonyl nickel powder is 1:2.9-3.2, preferably 1:3.0-3.2, and more preferably 1:3.0-3.1.

[0071] In the present invention, the pressure during pressing is 10 to 15 MPa, preferably 11 to 13 MPa, and more preferably 11 to 12 MPa. The pressing time may be 15 to 20 min, preferably 15 to 18 min, and more preferably 15 to 17 min.

[0072] According to one embodiment of the present invention, the loading amount of the iron-boron alloy powder as the anode catalyst of the direct borohydride fuel cell in the obtained wafer is 114-116 mg / cm 2 .

[0073] According to one embodiment of the present invention, the DBFC single cell is assembled as follows: the electrode prepared as above is used as the anode of the single cell, and the Pt electrode is used as the cathode of the single cell; the anode electrolyte is a mixed solution of 6 mol / L KOH and 0.8 mol / L KBH4, the cathode electrolyte is a mixed solution of 4 mol / L H2O2 and 0.5 mol / L H2SO4, and the diaphragm is Nafion N212.

[0074] The raw materials used in the following examples and comparative examples are described as follows:

[0075] The cast iron-boron alloy was purchased from Bomate Boron Alloy Co., Ltd. The mass ratio of Fe to B in the cast iron-boron alloy was 3.76:1.

[0076] Examples 1 to 2 and Comparative Examples 1 to 4

[0077] Prepare according to the parameters in Table 1. A planetary ball mill is used to ball mill the cast iron-boron alloy for a certain period to obtain a ball milled sample; the ball milled sample is dried at 40°C in a vacuum state for 8 hours to obtain an iron-boron alloy powder used as an anode catalyst for a direct borohydride fuel cell. After drying, the product is vacuum sealed for standby use. Among them, during ball milling, the ball milling medium is anhydrous ethanol, the balls used are large steel balls and small steel balls, the diameter of the large steel balls is 10mm, the diameter of the small steel balls is 6mm, the mass ratio of all large steel balls and all small steel balls is 0.76:1, the ball-to-material ratio is 4:1, and the ball milling speed is 320rpm. Among them, one cycle is set to first make the planetary ball mill rotate forward for 20 minutes, stand for 10 minutes, then make the planetary ball mill reverse for 20 minutes, and stand for 10 minutes, that is, one cycle is 1 hour.

[0078] Table 1

[0079]

[0080] The iron-boron alloy powders used as anode catalysts for direct borohydride fuel cells obtained in the above examples and comparative examples were characterized:

[0081] (1) The Empyrean X-ray diffraction (XRD) diffractometer produced by Malvern Panalytical of the Netherlands was used for the test. The step scanning method was used for the scan, and the measurement angle range was 2θ = 20° to 90°; the results are shown in Figure 1(a), Figure 1(b) and Table 2.

[0082] As can be seen from Figure 1(a), with the increase of ball milling time, the diffraction peaks of the iron-boron alloy product continue to widen. For detailed analysis, four obvious diffraction peaks at 37.670°, 41.143°, 45.043° and 47.821° are selected, which correspond to the (101), (111), (021) and (210) crystal planes for half-height width calculation, which are listed in Table 2. Figure 1(b) adjusts 2θ=20°~90° in Figure 1(a) to 2θ=30°~60°. It can be clearly seen from Figure 1(b) that with the increase of ball milling time, the half-height width of the (101), (111), (021) and (210) peaks is constantly increasing. At the same time, it can be seen from Table 2 that with the increase of ball milling time, the half-height width of the diffraction peak of the iron-boron alloy product has an increasing trend. The increase in the half-width of the diffraction peak indicates that the iron-boron alloy product gradually changes from a crystalline structure to an amorphous structure.

[0083] Table 2

[0084]

[0085] (2) The microstructure and composition information were characterized by scanning electron microscopy combined with energy dispersive spectrometer (SEM / EDS) (TESCAN MIRALMS, Czech Republic).

[0086] The SEM results are shown in Figure 2(d), Figure 2(e), Figure 2(a), Figure 2(b), Figure 2(c), and Figure 2(f). Figure 2(a) to Figure 2(c) It can be seen that with the increase of ball milling time, the microstructure of the iron-boron alloy product gradually changes from a large block with neat edges and regular shapes to a small block with neat edges and irregular shapes; the crystal structure of the product is damaged to a certain extent, and the product begins to gradually show an amorphous state. It can be seen from Figure 2(c) and Figure 2(d) that with the further increase of ball milling time, the neat structure of the microstructure of the iron-boron alloy product is further damaged, and its edges begin to show initial passivation. A small number of products appear in clusters, indicating further amorphous state; Figure 2(d) to Figure 2(f) It can be seen that with the increase of ball milling time, the particle size of the microstructure of the iron-boron alloy product is further reduced, the passivation degree of the product is further increased, more and more products appear in clusters, the overall structure of the product becomes more and more chaotic and blurred, and the amorphization degree of the product becomes more serious.

[0087] The mapping diagrams of the as-cast Fe-B0 alloy (the product of Comparative Example 1) and the ball-milled Fe-B8 alloy (the product of Example 2) and the EDS spectrum analysis (surface scan) of the as-cast Fe-B0 alloy (the product of Comparative Example 1) are shown in FIG. Figure 3(a) to Figure 3(g) . Specifically, the Mapping results of Comparative Example 1 are shown in Figures 3(a), 3(b), and 3(c), respectively, the Mapping results of Example 2 are shown in Figures 3(d), 3(e), and 3(f), and the EDS spectrum results of Comparative Example 1 are shown in Figure 3(g). Comparing the Mapping diagrams of the iron-boron alloy products that were not ball-milled and ball-milled for 80 cycles, it was found that before ball milling, the Fe, B, and O elements on the alloy surface were uniformly distributed, but after 80 cycles of ball milling, it can be clearly seen that the distribution of Fe and B elements has become obviously chaotic and sparse; this should be because the degree of amorphization of the product after ball milling increases, and the disorder of atoms increases, which makes the atomic distribution on the surface more chaotic, which is consistent with the analysis results of SEM. In addition, by comparing the Mapping before and after ball milling, it was found that the distribution of O elements after ball milling is more uniform and dense, which may be due to: ① With the increase of ball milling time, the particle size of the product itself decreases, and the product is more likely to come into contact with air, resulting in an increase in oxygen content; ② With the increase of ball milling time, the experimental time increases, which may cause more air to enter. In order to further analyze the relationship between ball milling time and oxygen content in the alloy product, EDS energy spectrum analysis (surface scan) was performed on the alloy products of the comparative example and the embodiment, and the analysis results are listed in Table 3. As can be seen from Table 3, with the increase of ball milling time, the content of O element in the product gradually increases. This shows that with the increase of ball milling time, the oxidation degree of the product becomes more and more obvious.

[0088] Table 3

[0089]

[0090] Example 3 - Preparation of Electrode as Anode

[0091] The iron-boron alloy powders obtained in Example 1, Example 2, and Comparative Examples 1 to 4 are respectively mixed with carbonyl nickel powder in a mass ratio of 1:3 to obtain a mixture. Weigh 1 g of the mixture and put it into a cylindrical mold with a diameter of 1 cm. Use a powder tablet press to maintain the pressure at a pressure of 11 MPa for 15 minutes and press it into small discs. Then wrap the small disc with foamed nickel of a size of 3 cm × 4.5 cm, and clamp one end of the nickel strip used as an electrode lead between the foamed nickel and spot weld it around it. This makes the electrode to be tested as the anode. The electrode to be tested is recorded as Fe-B / NF.

[0092] Experimental Example 1

[0093] Testing of Fe-B alloy powder on BH4 -Catalytic oxidation performance: Cyclic voltammetry (CV), chronoamperometry (CA) and electrochemical impedance spectroscopy (EIS) tests were carried out using an electrochemical workstation (from Shanghai Chenhua CHI660E).

[0094] During the test, a three-electrode system was used, with the working electrode being Fe-B / NF (the electrodes to be tested prepared in Example 3), the counter electrode being 3cm×3cm nickel foam (NF), and the reference electrode being Hg / HgO. The electrolyte was a mixed solution of 0.1mol / L KBH4 and 2mol / L KOH. The CV test range was -0.6 to 0.6V vs Hg / HgO, and the scan rate was 50mV / s. The CA test time was 60s, and the test range was -25 to 250mA / cm 2 The EIS test range is 0.1Hz~105Hz, the initial potential is the open circuit voltage, and the Nyquist plot obtained by the test is analyzed by equivalent circuit diagram using Zview 3 software. The results are as follows.

[0095] (1) CV test results

[0096] CV curve results are shown in Figure 4 The corresponding maximum oxidation peak current density and corresponding potential values ​​are listed in Table 4.

[0097] During testing, the loading of the iron-boron alloy powder as the anode catalyst for direct borohydride fuel cells was 114.8 mg / cm 2 , the scanning rate is 50mV / s. Figure 4 As shown in Table 4, all products have an oxidation peak, and the oxidation peak position is about -0.43V vs Hg / HgO. Comparing the oxidation peak current density, it is found that with the increase of ball milling time, the oxidation peak current density of the iron-boron alloy catalyst first increases and then decreases. The oxidation peak current density of the product in Example 2 reaches the maximum, which is 23.98mA / cm 2 It can be inferred that with the increase of ball milling time, the Fe-B alloy catalyst has a greater - The catalytic performance of the product of Example 2 is gradually enhanced, and the catalytic performance of the product of Example 2 is the strongest, which should be related to the degree of amorphization of the iron-boron alloy product caused by ball milling. However, it is also seen that when the ball milling time is too long, the oxidation peak current density of the product of Comparative Example 4 does not increase but decreases, which is lower than that of the product of Example 2. It is speculated that the ball milling time is too long, although the degree of amorphization increases, the iron-boron alloy powder is severely oxidized, resulting in a decrease in its catalytic performance.

[0098] Table 4

[0099]

[0100] (2) CA test results

[0101] Figure 5 The CA curves of BOR reaction catalyzed by Fe-B alloy at different ball milling times are shown in Table 4. Figure 5 As shown in Table 4, the CA curves corresponding to the iron-boron alloy catalysts with different ball milling times are relatively flat as a whole, and with the increase of the ball milling cycle, the stable current density value of the iron-boron alloy product first increases slowly and then decreases. Among them, the product of Example 2 after 80 cycles of iron-boron alloy ball milling has a maximum stable current density value of 12.29 mA / cm 2 The stable current density of the alloy decreased after that; when the ball milling time reached 100 cycles, the stable current density of the product of Comparative Example 4 decreased to 10.48 mA / cm 2 This indicates that the iron-boron alloy product is relatively stable as a catalyst during the catalytic process, and the product of Example 2 has the lowest energy loss during the catalytic process, which is consistent with the above CV test results.

[0102] (3) EIS test results

[0103] Figure 6 The EIS Nyquist plots of the BOR reaction catalyzed by the iron-boron alloy at different ball milling times are shown in Table 4. In the EIS plot, the larger the semicircle diameter, the greater the impedance. Figure 6 It can be seen from Table 4 that the impedance of the iron-boron alloy product shows a trend of gradually decreasing with the increase of ball milling time. The impedance of the product of Comparative Example 1 is the largest, which is 2.78Ω. The impedance of the product of Example 2 is very close to that of the product of Comparative Example 4, which are 2.32Ω and 2.16Ω respectively. With the increase of ball milling time, the amorphous degree of the iron-boron alloy product continues to increase. The greater the amorphous degree, the smaller the impedance.

[0104] Experimental Example 2- Single Cell Performance Test

[0105] In order to study the application performance of iron-boron alloy powder anode catalyst in DBFC fuel cells, a DBFC single cell was made to test its performance.

[0106] The assembly of DBFC single cell is as follows:

[0107] The electrode prepared in Example 3 is used as the anode of the single cell, and the Pt electrode is used as the cathode of the single cell. Specifically, the anode of the single cell is an electrode formed by the Fe-B 8 alloy powder of Example 2 and an electrode formed by the Fe-B0 alloy powder of Comparative Example 1;

[0108] The anolyte was a mixed solution of 6 mol / L KOH and 0.8 mol / L KBH4, the catholyte was a mixed solution of 4 mol / L H2O2 and 0.5 mol / L H2SO4, and the diaphragm was Nafion N212.

[0109] The single cell performance was tested at room temperature. The test results of polarization curve and power density are shown in Figure 7 .

[0110] from Figure 7 From the polarization curves, it can be seen that the open circuit potentials of the single cells formed by the Fe-B0 product of Comparative Example 1 and the Fe-B8 product of Example 2 are 1.755 V and 1.645 V, respectively, which are both lower than the theoretical potential value of DBFC, 3.01 V; this should be due to the BOR reaction and BH4 - The hydrolysis reaction proceeds simultaneously and mixes with its potential. In addition, the power density curve shows that the power density of the product after 80 cycles of ball milling (26.80 mW / cm 2 ) is significantly greater than the power density of the unmilled cast alloy (16.28 mW / cm 2 ). This is consistent with the fact that the stable current density value of CA and the maximum current density value of CV of the product of Example 2 tested above are both greater than those of the product of Comparative Example 1. This should be mainly due to the fact that with the increase of ball milling time, the amorphous degree of the product of Example 2 increases compared with the product of Comparative Example 1. It can be seen that the iron-boron alloy can be used as an anode catalyst for DBFC, and the amorphous iron-boron alloy prepared by the present invention exhibits better catalytic performance.

[0111] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.

Claims

1. A method for preparing an anode catalyst for a direct borohydride fuel cell, characterized in that: The steps include: The cast iron-boron alloy is ball-milled by a planetary ball mill for 60 to 80 cycles to obtain a ball-milled sample; the ball-milled sample is dried to obtain an iron-boron alloy powder used as an anode catalyst for a direct borohydride fuel cell; Wherein, the mass ratio of Fe to B in the cast iron-boron alloy is 3.5-4.0:1; The ball milling medium is anhydrous ethanol, the ball-to-material ratio is 3.5-4.5:1, and the ball milling speed is 300-400 rpm; Among them, one cycle is set to first make the planetary ball mill rotate forward for 18 to 22 minutes, stand for 7 to 11 minutes, and then make the planetary ball mill reverse for 18 to 22 minutes, and stand for 7 to 11 minutes.

2. The preparation method according to claim 1, characterized in that: The as-cast iron-boron alloy was ball-milled for 70 to 80 cycles using a planetary ball mill.

3. The preparation method according to claim 1, characterized in that: In the cast iron-boron alloy, the mass ratio of Fe to B is 3.6 to 3.9:

1.

4. The preparation method according to claim 1, characterized in that: The ball-to-material ratio is 3.7-4.2:

1.

5. The preparation method according to claim 1, characterized in that: During ball milling, a mixture of large and small steel balls is used, the diameter of the large steel balls is 8 to 10 mm, and the diameter of the small steel balls is 4 to 6 mm.

6. The preparation method according to claim 1, characterized in that: The ball mill speed is 300-350 rpm.

7. The preparation method according to claim 1, characterized in that: One cycle is set to first rotate the planetary ball mill forward for 19 to 21 minutes, stand for 9 to 11 minutes, then reverse the planetary ball mill for 19 to 21 minutes, and stand for 9 to 11 minutes.

8. A method for preparing an anode of a direct borohydride fuel cell, characterized in that: The steps include: (1) preparing an iron-boron alloy powder used as an anode catalyst for a direct borohydride fuel cell according to the preparation method described in any one of claims 1 to 7; (2) mixing the iron-boron alloy powder and carbonyl nickel powder obtained in step (1) to obtain a mixture; loading the mixture into a cylindrical mold and then pressing it into a disc; wrapping the disc with nickel foam, and then clamping one end of a nickel strip used as an electrode lead between the nickel foams and spot welding it around to obtain an electrode used as an anode; wherein the mass ratio of the iron-boron alloy powder to the carbonyl nickel powder is 1:2.9-3.

2.

9. The preparation method according to claim 8, characterized in that: The pressure during pressing is 10-15 MPa, and the pressing time is 15-20 min.

10. The preparation method according to claim 8, characterized in that: The loading of iron-boron alloy powder as anode catalyst for direct borohydride fuel cells in the disc is 114-116 mg / cm 2 .

Citation Information

Patent Citations

  • Application of Ni-based catalyst in anode of direct borohydride fuel cell

    CN101667645A

  • Preparation method and application of anode catalyst of direct borohydride fuel cell

    CN105655601A

  • Anode catalyst of direct borohydride fuel cell and preparation method thereof

    CN111952609A

  • Preparation method of Ag-modified La-Mg-Ni type hydrogen storage alloy and application of Ag-modified La-Mg-Ni type hydrogen storage alloy as DBFC anode catalyst

    CN113410476A